Tradisi Ondangan di Cigugur: Analisis Nilai Moderasi Beragama Berdasarkan Teori Empat Pilar Moderasi Beragama - Abdul Mun'em Choiri; Fikrul Maarif Saleh; Ida Farida; Irfandi Andika Putra; Irma Riyani; Salma Fauziah (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2025)
This study delves into the Ondangan tradition of Cigugur, a cultural practice rich in communal and spiritual significance, through the lens of the Four Pillars of Religious Moderation. The Ondangan tradition, deeply rooted in the social fabric of Cigugur offers a unique window into how religious moderation can be practiced and upheld in a diverse society. By employing a descriptive-qualitative approach, this research uncovers how the four pillars—national commitment, tolerance, non-violence, and cultural accommodation—are intricately woven into this tradition. The findings reveal that Ondangan not only nurtures social cohesion and mutual respect among diverse religious groups but also embodies a living example of how local traditions can harmonize with broader religious values. This study highlights the Ondangan tradition as a powerful model for fostering inclusivity, promoting peace, and preserving cultural identity in a pluralistic world.